THE EFFECT OF SONG LYRIC TEXT ON STUDENTS’ VOCABULARY MASTERY AT SEVENTH GRADE OF SMPI AL IKHLASH KASEMBON - Maharani Fitria; Novi Rina Dewi (English Language Teaching Journal, 2022)
This study was conducted to know the effectiveness of song lyric text on students’ vocabulary mastery at SMPI Al Ikhlash Kasembon in seventh grade. This study used pre-experimental research design with one experimental group only. The population in this research was seventh grade of SMPI Al Ikhlash Kasembon Malang consisting 24 students. The researcher used pre-test and post-test in multiple choice consisting 21 items format then the data was analyzed by t-test using SPPS version 30.After collecting data, the calculation of the data resulted the average (mean) score of pre-test and post-test.The mean score of pre-test was 25.0 with standard deviation was 14.166. Meanwhile, the mean score of post-test was 76.0 with standard deviation was 25.160. In testing hypothesis, the researcher used t-test formula. The result of t-test is -10.345 at the level of significance of DF is 23 and the Sig. (2-tailed) is 0.00 at the 95% confidence interval of the difference. Based on SPSS, the result is 0.00<0.05. The Sig. (2-tailed) was lower than 0.05 so it means that there was significant between pre-test and post-test. So, the null hypothesis (H0) was rejected and the alternative hypothesis could be accepted. It means that the using of Song lyric text give positive effect to the students’ vocabulary. Keywords: Song Lyric Text, Vocabulary